Adaptive and optimized COVID-19 vaccination strategies across geographical regions and age groups - Molla, Jeta; Ponce de León Chávez, Alejandro; Hiraoka, Takayuki; Ala-Nissila, Tapio; Kivelä, Mikko; Leskelä, Lasse (PLOS Computational Biology, 2022)
Author summary The COVID-19 vaccines are now available worldwide and many countries follow the practice of distributing them heuristically e.g. in age-descending order and demographically. Here we evaluate the effectiveness of such strategies by comparing them with optimized ones from an age and spatially-structured mathematical model of COVID-19 transmission. We find that vaccinating multiple age groups simultaneously and targeting regions with the the highest incidence can save more lives than heuristic strategies. Our work also reveals the importance of assessing the vaccination strategy at different stages of the epidemic.